Adalimumab drug induced pulmonary infiltrates and eosinophilia. Issue 1 (2nd January 2019) - Tallon, Kelsey; Cockcroft, Donald
Abstract: Adalimumab (Humira) is a recombinant monoclonal antibody that binds to human tumour necrosis factor alpha (TNF-alpha) and, consequently, interferes with the cytokine-driven inflammatory process. It is used to treat a number of conditions including ankylosing spondylitis, Crohn's disease, ulcerative colitis, plaque psoriasis, psoriatic arthritis and rheumatoid arthritis. One of the rare side effects of adalimumab is interstitial lung disease. Our case report is a 61-year-old female who was referred for increasing intermittent wheezing, dyspnea and cough with a many year history of asthma. She had received 3 (monthly) doses of adalimumab for her Crohn's disease. Imaging revealed patchy densities bilaterally. Her blood count had an elevation of eosinophils. With cessation of the medication the pulmonary infiltrates resolved and her blood eosinophilia returned to normal. Given that the investigations for eosinophilic granulomatosis with polyangiitis (EGPA) and allergic bronchopulmonary aspergillosis (ABPA) were negative this was highly suspicious for an adalimumab drug induced pulmonary infiltrates and eosinophilia. There is a paucity of reports of eosinophilic induced lung disease associated with adalimumab. The pneumotox.org registry has eosinophilic pneumonia listed as a pattern of disease with less than 10 cases reported from a (suspected) drug reaction to adalimumab. This case gives strength to suggestion that adalimumab is an offending drug that may cause pulmonary infiltrates and eosinophilia.